2019
DOI: 10.1002/iub.2044
|View full text |Cite
|
Sign up to set email alerts
|

miR‐146a‐5p enhances hepatitis B virus replication through autophagy to promote aggravation of chronic hepatitis B

Abstract: The objective of this study was to investigate the mechanism by which miR‐146a‐5p mediated autophagy and hepatitis B virus (HBV) replication. Quantitative real‐time polymerase chain reaction (qRT‐PCR) was used to determine the mRNA expression levels of miR‐146a‐5p and X‐linked inhibitor of apoptosis (XIAP) and HBV DNA and RNA. The protein expression levels of XIAP, IκB‐α, murine double minute 2 oncoprotein (MDM2) and p53, the phosphorylation of p65, and the conversion of light chain 3 (LC3)‐I to LC3‐II were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Among these three miRNAs, miR-146a-5p and miR-328-3p could distinguish ACLF from non-ACLF (ASC and CHB) with high values of specificity and sensitivity [9]. We have also previously demonstrated that miR-146a-5p enhances HBV replication through autophagy to promote aggravation of CHB [10]. MiR-146a has been shown to directly target CXCR4 [11], a gene involved in the advanced liver disease that is associated with hepatitis C virus or HBV [12].…”
Section: Introductionmentioning
confidence: 90%
“…Among these three miRNAs, miR-146a-5p and miR-328-3p could distinguish ACLF from non-ACLF (ASC and CHB) with high values of specificity and sensitivity [9]. We have also previously demonstrated that miR-146a-5p enhances HBV replication through autophagy to promote aggravation of CHB [10]. MiR-146a has been shown to directly target CXCR4 [11], a gene involved in the advanced liver disease that is associated with hepatitis C virus or HBV [12].…”
Section: Introductionmentioning
confidence: 90%
“…miR-146a-5p promoted HBV replication through the XIAP-mediated MDM2 (mouse double minute 2 [MDM2])/p53 autophagy pathway to promote aggravation of chronic hepatitis B. 142 Enterovirus 71 (EV71) is a group of viruses that belongs to the Picornaviridae family and is the principal causative agent of severe and fatal hand, foot, and mouth disease. Overexpression of miR-30a could suppress EV71 replication by blocking EV71-induced autophagy.…”
Section: Mirs Regulate Autophagy In Viral Diseasesmentioning
confidence: 99%
“…p53 is one of the most intensively studied tumor suppressor proteins. miR‐146a‐5p promoted HBV replication through the XIAP‐mediated MDM2 (mouse double minute 2 [MDM2])/p53 autophagy pathway to promote aggravation of chronic hepatitis B …”
Section: Introductionmentioning
confidence: 99%
“…The present cross-sectional observational study expressed that higher increasing ADAMTS13 and IL-12 levels, but not the baseline levels of ADAMTS13 and IL-12, were significantly and positively associated with the prevalence of HBeAg SC in CHB patients during 96-week m-ETV treatment, suggesting higher increasing plasma ADAMTS13 (IL-12) level as a definite probability for HBeAg SC, independent of other factors, such as HBV DNA, HBsAg, HBeAg, and VWF, although the VWF level is closely related to ADAMTS13 concentration in the peripheral blood of CHB patients. There are many literatures about the pathogenesis of patients with chronic HBV infection, and the imbalance of a coagulation system also plays an important role in CHB pathogenesis (Saray et al, 2012;Chang and Liu, 2016;Fu et al, 2019). Von Willebrand factor is a member of the main proteins involved in hemostasis and thrombosis in the body.…”
Section: Discussionmentioning
confidence: 99%